Semiotics of Sufi Texts- Poets of Al Qasr and Al-Asr journals as a Model - فياض, اسراء خليل; أحمد, زينب فاضل (ALBAHITH ALALAMI, 2016)
In a common language based on interpretation and diagnosis in the symbols and signs, the subject of Sufism and artistic semiotics is manifested in the construction and intensity of the reading of the text and the dismantling of its intellectual systems.The emergence of Sufism in its religious features and the spiritual revelations related to the divine love of life in absolute reality, And images and language in a stream of intellectual and artistic unique and harmonious communicates with the subject of the themes of the Arab literature and its implications, but it is separated by a special entity signals and symbols related to the mysticism and worship.    The unleashing of the imagination and the diagnosis, and the Tijsim was a repository from which Sufism derives the powers of the soul and its primary material through the formation of the world of images and intended divine names and divine self. Which helped them in their words and their efforts to find a special language depends on the symbol in the expression of their ideas is the meaning of the soles of stock under the words of the apparent can only be achieved by the family in its public form calls for ambiguity and concealment. And within the mechanisms of producing a new text, but what appeared in the form of external show us continue to meet the semiotics with the language of Sufism between the capacity of thought and deciphering symbols, to show us the mystical text signals and forms within the space of plastic modernism.   The Sufi text has taken on a distinctive character in its different formations of different poets and their different experiences. Hence, the study was of an analytical and semi-descriptive nature within the cells of Sufi symbols of wine, nature, beauty, and journeys to the Divine Self and the Sufi Sufi. This research came in two frameworks, the first of which was the induction framework which came to be known in various terms such as semiotics and mysticism, as well as the book Al-Khuraida. The second is to be the analytical framework.